2015
DOI: 10.4067/s0718-27242015000300013
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lean Manufacturing Tools in the Food and Beverage Industries

Abstract: Abstract:Recent years have shown an increasing use of lean manufacturing (LM) principles and tools in several industrial sectors. Already a wellestablished management philosophy, it has shown numerous successful applications even outside production environments. This work presents the application of some LM tools, and the corresponding shift in philosophy, in two Portuguese companies of the food and beverage industries. Main implementation issues are presented and discussed; followed by the results obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 24 publications
4
23
0
5
Order By: Relevance
“…The key benefit revealed to be decreasing the inventory level. Improving the supply chain flexibility, eliminating wastes and reducing the cycle times are added benefits to include and these finding also align with the literature (Bruce et al, 2004;Achanga et al, 2006;Womack et al, 2007;Cudney and Elord, 2011;Borges Lopes et al, 2015). Interestingly, the drivers related to providing great customer satisfaction and increasing the profits were ranked low, in agreement to the understanding of basic lean depicted in previous section.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The key benefit revealed to be decreasing the inventory level. Improving the supply chain flexibility, eliminating wastes and reducing the cycle times are added benefits to include and these finding also align with the literature (Bruce et al, 2004;Achanga et al, 2006;Womack et al, 2007;Cudney and Elord, 2011;Borges Lopes et al, 2015). Interestingly, the drivers related to providing great customer satisfaction and increasing the profits were ranked low, in agreement to the understanding of basic lean depicted in previous section.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, Ugochukwu et al (2012) pointed out that lean is a management approach that attempt to organize the human activities to deliver more added values to customers while eliminating waste inside and afar organizations value chain. It is an approach to monitor and control the waste inadvertently generated by a specific process to accomplish cost lessening, quality and proficiency optimization with less exertion (Borges Lopes et al, 2015). By reviewing the preceding literature, it can be concluded that there are alternate perspectives on the emergence of the lean concept.…”
Section: Literature Review the Lean Conceptmentioning
confidence: 99%
“…As mentioned by [30], the company has sought to innovate its production process by adopting the industrial management technique Lean Manufacturing. For such, this knowledge transfer has been efficiently established with the assistance of the LKT team, made up of collaborators from two Federal Higher Education Institutions and the company in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits brought forth by implanting this industrial management technique, according to [4], are reduction of production costs, of lead time and improvement of production flow. Additionally, [30] stress that this technique has been shown as a good example of innovation in enterprises and one of its supports is the continuous improvement. However, so as to explore Lean, firstly, a current Value Stream Mapping (VSM) must be carried out in the production process aiming to show the wastes inherent to the process and then point out improvement opportunities in the future state or expected state VSM [12].…”
Section: Introductionmentioning
confidence: 99%
“…The overall performance of this line was found to be below the target, hence the need for improvement was necessary to achieved this, is by making a study of the process analysis in order to consider every part of the production line as well as analyzing the data to detect the possible failures of the production line. Rui et al [2] applied lean manufacturing techniques in a food and beverage industries to improve their productivity by sensitizing the employees on the importance of lean concepts and the implementation. The employees were informed and trained on the 5S methodology on several work stations.…”
Section: Introductionmentioning
confidence: 99%